Sesquiterpenes from marine sponge Dysidea fragilis - Kiem, Phan Van; Cuc, Nguyen Thi; Thuy Hang, Dan Thi; Dung, Duong Thi; Nhiem, Nguyen Xuan; Tuan Anh, Hoang Le; Yen, Pham Hai; Thung, Do Cong; Minh, Chau Van (Vietnam Journal of Chemistry, 2015)
By various chromatographic separations, three sesquiterpenes, furodysinin lactone (1), O-methyl furodysinin lactone (2) and  O-methyl-9-oxofurodysinin lactone (3) were isolated from Vietnamese marine sponge Dysidea fragilis. Their structures were determined by 1D-, 2D-NMR spectra and in comparison with the reported data. Compound 3 was reported from sponge D. fragilis for the first time.